Prioritizing sites for gas distribution system decommissioning projects using geospatial data and decision support tools - Eric D. Fournier; Jacob Moul; Maya Ofek; Julia Skrovan; Spencer Mathews; Robert Cudd; Stephanie Pincetl (Utilities Policy, 2026)

Assessment of Corn Husk Biochar-Amended Coix lacryma-jobi-planted Constructed Wetland for Sustainable Jabi Lake Water Treatment - Davids Olorungbon Raphael; Williams S. Olotu; Olusegun K. Abass; Oluwaseyi Mathew Abioye; Olumoyewa D. Atoyebi (Water Conservation Science and Engineering, 2026)

Seed bio-priming with multifaceted PGPR from underutilized medicinal plants enhances disease resistance and improves yield in rice - S. Raghu; B. Jeevan; Devayani Sarmah; Mathew Baite; C. Anilkumar; Rupak Jena; M. K. Bag; B. S. Satapathy; S. D. Mohapatra (Australasian Plant Pathology, 2026)

Introgression of teosinte branched1 gene from wild-progenitor enhances prolificacy in subtropically-adapted maize - Firoz Hossain; Rajkumar Uttamrao Zunjare; Rashmi Chhabra; Irum Gul; Amitkumar D. Kyada; Elizabeth Mathew; Ravindra K. Kasana; Nitish R. Prakash; Vinay Bhatt; Sunil Neelam; Vignesh Muthusamy (Planta, 2026)

Use of translational fusions to express functional Klebsiella oxytoca dinitrogenase reductase in plant mitochondria - Shoko Okada; Xueqin Wang; Christina M. Gregg; Robert S. Allen; Timothy Rhodes; Vanessa Gillespie; Ingrid Venables; Anu Mathew; Jessica K. Bilyj; Keren Byrne; Robert C. DeFeyter; Trevor D. Rapson; et al. (Plant Molecular Biology, 2026)
Engineering crop plants with the biological nitrogen fixation pathway is a longstanding goal of modern agriculture. Dinitrogenase reductase (NifH) is a critical component of the biological nitrogen fixation pathway, with multiple roles in metal cofactor assembly and catalysis. This enzyme must be folded correctly as a soluble homodimer and loaded with the [4Fe-4S] metallocluster for function. Previous studies have found that Klebsiella oxytoca ( Ko ) and Azotobacter vinelandii ( Av ) NifHs were mostly insoluble when targeted to plant mitochondria. Here we found that a translational fusion of two Ko NifH or Av NifH monomers, forming Ko NifHH or Av NifHH synthetic dimers, produced a soluble protein when targeted to plant mitochondria and co-expressed with the putative peptidyl-prolyl cis–trans isomerase NifM. Ko NifHH isolated after expression in leaf mitochondria at ambient oxygen showed some acetylene reduction activity, which did not require co-expression of the nitrogenase-specific metallocluster machinery NifS and NifU. This activity increased after iron-sulfur cluster reconstitution in vitro with recombinant NifU. In a parallel study, we tested a translational fusion of a variant iron-only dinitrogenase reductase ( Av AnfHv6) monomer that was soluble but not active as-isolated from plant mitochondria ( Av AnfHHv6) (Gregg et al. 2025a). Av AnfHHv6 was abundant and fully soluble when isolated from plant mitochondria, like its monomer. Av AnfHHv6 was not active as-isolated but could be largely activated by iron-sulfur cluster reconstitution in vitro. This study demonstrates how translational fusions help improve solubility and have the potential to generate an active NifH enzyme within plant mitochondria.

Age-related differences in motor unit discharge rate modulation across contraction levels - Christopher D. Connelly; Tamara Valenčič; Haydn Thomason; Ed Sadula; Gregory E. P. Pearcey; Mathew Piasecki; Jonathan P. Folland; Jakob Škarabot (GeroScience, 2026)
Age-related strength loss may reflect morphological and neural adaptations that differ between muscles. However, it is unclear how ageing affects motor unit (MU) discharge rate modulation and estimates of persistent inward currents (PICs) across contraction levels. Thirty young (24 ± 4 years) and thirty older adults (73 ± 4 years) underwent magnetic resonance imaging and performed unilateral isometric dorsiflexion and knee extension contractions. Individual MU spike trains were identified from decomposed high-density electromyography recordings of tibialis anterior (TA) and vastus lateralis (VL) during triangular contractions at 30%, 50%, and 70% of maximal voluntary force (MVF). Older adults exhibited lower isometric strength in both tasks and smaller quadriceps but greater shank anterior compartment cross-sectional area compared to young. TA MU discharge rate was lower in older adults at all contraction levels but only at ≤ 50% MVF in VL. Discharge rate hysteresis (∆F), an estimate of PIC contribution to MU discharge, was lower in older adults at all TA contraction levels, but only at 70% MVF in VL, and in both muscles older adults exhibited an attenuated increase in ∆F across contraction levels. The ascending discharge rate non-linearity did not differ between groups, except at 30% MVF in VL where it was greater in older adults. Older adults also exhibited lower acceleration and attenuation slopes in TA, but not VL. These results reveal muscle-specific differences in MU discharge rate modulation with ageing, suggesting that the age-related strength loss is likely underpinned to a greater extent by morphological and neural factors in knee extensors and dorsiflexors, respectively.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A general hidden Markov model framework for capturing changes in species behaviour under disturbance in acoustic time series - Litty Mathew; Caroline Brophy; Ian Donohue; Samuel RP-J Ross; Silvia D'Angelo (Ecological Modelling, 2026)

Attitudes of Algorithms: An Exploration of the Ethics of CRISPR Cas9 through the Lens of ChatGPT - Russell Franco D’Souza; Mary Mathew; Krishna Mohan Surapaneni (Indian Journal of Clinical Biochemistry, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Improving growth traits in rabbits: a comparative study of Gabali, New Zealand White, and their hybrids using 18S rDNA sequencing - Hairul Islam Mohamed Ibrahim; Abdullah Sheikh; Roshmon Thomas Mathew; Muhammad Munir; Gamal Bekhet; El-Sayed Hemdan Eissa; Sameh A. Abdelnour; Mohamed D. Mahran (Tropical Animal Health and Production, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Generation of iPSC-Derived iNKT Cells with Pro-Hematopoietic Activity - Akhilesh Kumar; Sarah Ferguson; Saritha S. D’Souza; Nikhila S. Bharadwaj; Mathew Raymond; Jenny E. Gumperz; Igor I. Slukvin (Stem Cell Reviews and Reports, 2026)
Human invariant natural killer T (iNKT) cells are a conserved population of innate-like T cells that are activated by glycolipid antigens. In addition to their well-known role in anti-tumor function, iNKT cells are also involved in regulating and maintaining hematopoiesis in the bone marrow. Here, we present the reprogramming of human CD4 + Vα24 + Vβ11 + iNKT cells into induced pluripotent stem cells (iNKT-iPSCs) and describe a novel chemically defined, feeder-free 3D spheroid method for generating CD34 + cells from iNKT-iPSCs, followed by their re-differentiation into functional Vα24 + Vβ11 + iNKT cells (i-iNKT) with pro-hematopoietic activity. The i-iNKT cells showed specific binding to CD1d tetramers loaded with the lipid antigen α-galactosylceramide and had a similar transcription factor profile to that of somatic CD4 + iNKT cells. Additionally, in response to CD3 stimulation, the i-iNKT cells produced cytokines with hematopoietic potential and promoted expansion/differentiation of myeloid progenitors. These findings suggest the feasibility of using iPSCs as off-the-shelf i-iNKT cell sources to enhance the hematopoietic activity of bone marrow after hematopoietic stem cell (HSC) transplantation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Understanding the role of pluralistic ignorance in biodiversity conservation: A research agenda - Sandra J. Geiger; Hirotaka Imada; Carya Maharja; Nattavudh Powdthavee; Valeria Vitale; Lei Zhang; Claudio D. Rosa; Zenith N.C. Delabrida; Kristian S. Nielsen; Franz Essl; Mathew P. White (Global Environmental Change, 2025)

Assessing air pollution in a coastal urban setting: contributions of PM₁₀, vehicular emissions, and public health impacts - D. S. Reshmy; K. Swarnalatha; Sneha Gautam; Binu Sara Mathew; Prashant Hegde (Journal of Atmospheric Chemistry, 2025)

Ecological Risk–Benefit Analysis for Assisted Colonization - Rafael D'Andrea; György Barabás; Sarah E. Dalrymple; Wendy Foden; Piero Genovesi; Meghna Krishnadas; Mathew A. Leibold; Mark A. McPeek; Axel Moehrenschlager; Jon Paul Rodriguez; H. Reşit Akçakaya (Global Change Biology, 2025)
Assisted colonization (AC), translocating a species outside its indigenous range to avoid its extinction, is one of the few conservation options for some species. It is also controversial because of the history of ecological impacts of invasive species, including the extinction of native species as a result of novel ecological interactions resulting from the introduction. Although several national and international organizations have issued guidelines related to AC, none allow case‐specific decision‐making based on risks and benefits to biodiversity. We propose a two‐pronged approach to fill this gap. The first step aims to separate clear‐cut cases of AC from those that require an in‐depth risk analysis. We propose a set of seven qualitative criteria to identify AC projects that are clearly low‐risk and high‐benefit, and therefore should not be controversial, and those that are clearly high‐risk or low‐benefit and therefore should not be attempted. This identifies only the most obvious cases, leaving out many cases to be determined through a quantitative analysis to estimate the probabilities of extirpation of the resident species because of AC, which is the second step of our approach. We propose a roadmap for developing such a system based on community ecology theory, and a framework for considering the estimated probabilities in a global context. Our framework recommends an AC project only if it would result in a larger number of globally extant species than a scenario of no action. We propose large‐scale testing of the clear‐cut approach, further development of the quantitative approach, and wide consultation for adopting international guidelines for risk assessment of AC projects.

Motivations and barriers to integrated management of annual bluegrass in sports fields: US survey findings - David E. Ervin; George B. Frisvold; Jennifer H. Allen; Aaron J. Patton; James T. Brosnan; Rebecca Grubbs Bowling; Mathew T. Elmore; Muthukumar V. Bagavathiannan; James D. McCurdy; Travis W. Gannon; John E. Kaminski; Alec R. Kowaleski; et al. (Urban Forestry & Urban Greening, 2025)

Impact of an Adapted Group Lifestyle Balance Program on Weight Loss and Physical Activity Uptake Among Adolescent Bariatric Surgery Patients - M. Misserian; F. Jackson; A. Wheelington; R. King; M. Mathew; M. Allicock; B. Cartwright; A. Chandrasekhar; D. Polavarapu; F. Qureshi; S. Barlow; S. Messiah (Journal of the Academy of Nutrition and Dietetics, 2025)

Deep learning assisted denoising of fast polychromatic X-ray micro-CT imaging of multiphase flow in porous media - E.S. Mathew; S.J. Jackson; D. Wildenschild; P. Mostaghimi; K. Tang; R.T. Armstrong (Computers & Geosciences, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Satellite tracking reveals sex-specific differences in the geographical and vertical habitat use of Whale sharks, Rhincodon typus, in the Eastern Indian ocean - Colby J. Bignell; Toby A. Patterson; Anthea Donovan; Mathew A. Vanderklift; Wayne Rochester; Jayson M. Semmens; Richard D. Pillans (Marine Biology, 2025)
Satellite tagging of whale sharks ( Rhincodon typus) has typically focused on juvenile males which dominate coastal aggregation sites, with limited data on the movements of females. We satellite-tagged 39 whale sharks of 3.75–9.27 m total length at Ningaloo reef between 2015 and 2018 with a roughly equivalent sex ratio (Male = 20, Female = 18, Unknown = 1).We aimed to identify differences in horizontal and vertical movements between the sexes using state-space models, kernel utilisation distributions (KUDs) and generalised additive models (GAMs). Deployment spans ranged from 9 to 340 days (mean = 132.4 ± SE = 17.9 days, N = 35) and 22 tracks exceeded 1000 km in length (mean = 2557 ± SE = 370 km, N = 35). Whale sharks spent > 90% of time in epipelagic waters ≤ 200 m and dived to a maximum depth of 1906 m. Sex-specific differences in horizontal and vertical movements were related to distinct temperature preferences. Females spent more time in offshore waters and preferred cooler Sea Surface Temperatures (SST) than males. Female movements were strongly influenced by increasing SSTs with greater space and depth use, while the space and depth use of males was more consistent with SSTs < 28 °C. We found no relationships between whale shark size and their space, depth or temperature use, though most individuals were immature (< 8 m, N = 24). The results provide novel evidence of sex-specific horizontal and vertical movements over broad geographical scales, extending current knowledge on the movement ecology and sex-specific demography of this endangered species.

Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

How you dune-ing? a systematic review of coastal dune plant community assembly - Ben J. Rivera; Jamie Belone; Alice R. Mathew; Kassandra Vega; Sofia N. Mosqueda; Dylan S. Sommer; Pete D. Maciel-Martinez (Journal of Coastal Conservation, 2025)
Coastal dunes are among the most imperiled ecosystems and are prime examples of ‘bio-geomorphologic’ systems wherein geomorphology impacts the vegetation and vegetation impacts geomorphology. This leads to distinct plant communities that trap sand differently which branches into different outcomes in dune shape, size, services, and biodiversity. Understanding how these plant communities form is crucial to protecting and restoring these vital ecosystems. In this review, we examine the history of coastal dune plant community assembly theory from Cowles’ early concepts of succession to modern theories. We found that coastal dunes have had a critical impact on assembly theory history by building on both successional and niche theories throughout the 1900s, but less so in recent years. To quantify and confirm these impressions, we performed a systematic review using the search term “Coastal Dune Community Assembly”, which yielded 37 papers. The ‘Environmental Filtering Metaphor’ was the most common assembly theory discussed (38%) followed by niche theory (19%) and the Stress-Gradient Hypothesis (16%). Notably, only 49% of the papers statistically tested these theories. Despite the overall lack of literature addressing dune plant community assembly, our synthesis suggests possible avenues of future study. There appears to be mixed and contradictory support for the Stress-Gradient Hypothesis, which future efforts should seek to disentangle. Additionally, the potential for the integration of functional traits is often noted as a promising direction (38%). More studies directly testing assembly theories and syntheses seem to be a promising direction in the protection and restoration of coastal dunes across the globe.

Comprehensive review of bacterial death mechanism on nanopillared nanostructured surfaces - Dimuthu Wijethunge; Asha Mathew; Prasad K. D. V. Yarlagadda (Biophysical Reviews, 2025)
Antibiotic resistance presents a significant global concern, worsened by overuse and limited development of new antibiotics. Medical implants, in particular, are increasingly susceptible to bacterial infections. To prevent biofilm formation on implants, it is essential to design specialized surface characteristics that either kill bacteria or inhibit their growth. Nanostructures resembling those found in nature, such as cicada wings, exhibit pronounced antibacterial efficacy. Drawing inspiration from these natural surfaces, artificial nanostructures made with similar features have demonstrated bactericidal effect. The bactericidal mechanism in nanostructures may seem simple, as the nanofeatures pierce through bacterial cells, leading to their death. However, research has shown that it is more complex and requires thorough investigation. Several studies indicate that while the bactericidal mechanism is initiated by mechanical contact, the precise killing process remains uncertain. Numerous experimental and theoretical investigations have aimed to elucidate the exact killing mechanism, yielding diverse conclusions and hypotheses, including cell death attributed to creep failure, motion-induced shear failure, apoptosis-induced programmed cell death and autolytic cell death, among others. This study undertakes a comprehensive review of all proposed death mechanisms. Moreover, it draws conclusions on the killing mechanism by meticulously analyzing the properties of bacterial membranes, their mechanosensing and adhesion mechanisms, energy-based models for bacterial adhesion, and experimental outcomes regarding the bactericidal efficacy of surfaces exhibiting diverse geometries. Graphical Abstract

Experimental pathways of clay formation and kinetics of basalt alteration in poor drainage systems: Implications for weathering - Piyush Sriwastava; Vijay Kumar Saini; George Mathew; Anil D. Shukla (Geochimica et Cosmochimica Acta, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Conservation translocation immediately reverses decline in imperiled sage-grouse populations - Mary B. Meyerpeter; Peter S. Coates; Megan C. Milligan; Brian G. Prochazka; Kade D. Lazenby; Steve Abele; John Tull; Katherine Miller; Jesse Kolar; Steven R. Mathews; David K. Dahlgren; David J. Delehanty (Biological Conservation, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Transdisciplinary Collaborations for Advancing Sustainable and Resilient Agricultural Systems - Vesna Bacheva; Imani Madison; Mathew Baldwin; Justin Baker; Mark Beilstein; Douglas F. Call; Jessica A. Deaver; Kirill Efimenko; Jan Genzer; Khara Grieger; April Z. Gu; Mehmet Mert Ilman; et al. (Global Change Biology, 2025)
Feeding the growing human population sustainably amidst climate change is one of the most important challenges in the 21st century. Current practices often lead to the overuse of agronomic inputs, such as synthetic fertilizers and water, resulting in environmental contamination and diminishing returns on crop productivity. The complexity of agricultural systems, involving plant‐environment interactions and human management, presents significant scientific and technical challenges for developing sustainable practices. Addressing these challenges necessitates transdisciplinary research, involving intense collaboration among fields such as plant science, engineering, computer science, and social sciences. Five case studies are presented here demonstrating successful transdisciplinary approaches toward more sustainable water and fertilizer use. These case studies span multiple scales. By leveraging whole‐plant signaling, reporter plants can transform our understanding of plant communication and enable efficient application of water and fertilizers. The use of new fertilizer technologies could increase the availability of phosphorus in the soil. To accelerate advancements in breeding new cultivars, robotic technologies for high‐throughput plant screening in different environments at a population scale are discussed. At the ecosystem scale, phosphorus recovery from aquatic systems and methods to minimize phosphorus leaching are described. Finally, as agricultural outputs affect all people, integration of stakeholder perspectives and needs into research is outlined. These case studies highlight how transdisciplinary research and cross‐training among biologists, engineers, and social scientists bring diverse expertise to tackling grand challenges in sustainable agriculture, driving discovery and innovation.

Textural characteristics of channel bed sediments and heavy minerals of the Cauvery River, Southern India: implications on depositional environments, provenance, tectonics and climate - M. Ramkumar; AL Fathima; G. Sugavanam; B. Velliyangiri; M. Selvakumar; S. Anbarasan; M. Sowmiya; S. Kiruthika; K. Balasubramani; V. Thirukumaran; P. D. Roy; R. Nagarajan; et al. (Journal of Sedimentary Environments, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Ecosystems managed for wildlife and livestock: Contrasting herbivore impacts in a heavily grazed African savanna - Michael D. Voysey; Sally Archibald; Mathew A. Harris; Gareth P. Hempson; Michelle Greve (Journal of Arid Environments, 2024)

Neck extensor myopathy- a treatable cause of dropped head syndrome - Nibu Varghese; Vimal Chandraghosh K D; Deepak Menon; Abdurahiman P; Anoop Kattadimmal; Jubin Mathew; Shobika B S; Nyla Mary Babu (Acta Neurologica Belgica, 2024)

A new species of an endemic termite Ampoulitermes zacharia sp.nov (Blattodea: Isoptera: Termitidae: Nasutitermitinae) from Idukki, Kerala, India - Edwin Joseph; Sony Joseph; V. P. Sandra; M. D. Jerin; Anita Binu; B. Radhika; S. Samyuktha; Liz Merin Renjith; Jobin Mathew (International Journal of Tropical Insect Science, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Revitalizing dredged soils through chemical-physical combined method: A feasibility study - Kishore M S; Gayathri S; D. Akhil Varma; Jeevan Mathew Tharayil (Marine Georesources & Geotechnology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Nutrient dynamics and sustainability of short rotation Eucalyptus camaldulensis plantations in southern India - Roby Mathew; D. S. Guru Murthy; Mohan Varghese (New Forests, 2024)

Extreme iron cycling in a coastal lake-lagoon system driven by interactions between climate and entrance management - Scott G. Johnston; Thor Aaso; Damien T. Maher; Edward D. Burton; Mitchell Call; Mathew Birch; John Schmidt; Angus Ferguson (Science of The Total Environment, 2024)

Cannabis use in Parkinson’s disease: Patient access to medical cannabis and physician perspective on product safety - Symone T. Griffith; Kendra D. Conrow; Michael Go; Mindy L. McEntee; Raminta Daniulaityte; Majia H. Nadesan; Mathew R. Swinburne; Holly A. Shill; Maxwell C.K. Leung (NeuroToxicology, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Isolation of intake mediated effects demonstrate that the phenomic benefits of dietary omega-3 are nominal to Atlantic salmon when reared in a challenging (hypoxic) environment - Brett D. Glencross; Alex Berry; Ben Clokie; Ernst Hevroy; David Huyben; Laura Martinez-Rubio; Chessor A. Mathew; Pedro Munoz; Simon MacKenzie; Rod W. Wilson (Aquaculture, 2024)

Normobaric hypoxia does not influence the sural nerve cutaneous reflex during standing - Mathew I. B. Debenham; Christina D. Bruce; Juliana M. Rancier; Chris J. McNeil; Brian H. Dalton (Experimental Brain Research, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Multi-instrument study of a spread-F event at Arecibo linked to solar wind variations - Salih Mehmed Bostan; Julio V. Urbina; John D. Mathews; Ross L. Dinsmore; Robert M. Robinson (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Progesterone-stimulated endometrial cell conditioned media increases in vitro produced bovine embryo blastocyst formation - Mary A. Oliver; Katie D. Peterson; Sadikshya Bhandari; Rebecca R. Payton; J. Lannett Edwards; Daniel J. Mathew (Animal Reproduction Science, 2023)

Differential methylation between sex in adult green sea turtle skin biopsies - Benjamin Mayne; Walter Mustin; Vandanaa Baboolal; Francesca Casella; Katia Ballorain; Mathieu Barret; Mathew A. Vanderklift; Anton D. Tucker; Oliver Berry (Frontiers in Marine Science, 2023)
In marine turtles, the sex of hatchlings is determined by their egg incubation temperature. Global warming may increase the extinction risk by skewing hatchling sex ratios. Assessment of this risk at the population level requires the identification of sex in hatchlings and juveniles. However, available methods are typically lethal, highly invasive, or difficult to conduct at a large scale. Changes in DNA methylation, an epigenetic modification, have been characterized as part of sex differentiation pathways in some species with environmentally determined sex, but so far not in marine turtles. Neither have epigenetic biomarkers for sex been developed into rapid assays suited to research on wildlife. In this study, we aimed to develop a rapid, minimally invasive, and inexpensive method to identify the sex of marine turtles. We used reduced representation bisulfite sequencing DNA methylation data from adult green sea turtle ( Chelonia mydas ) skin biopsies to identify 16 genomic regions exhibiting differential methylation between males and females (adjusted p-value < 0.01). We designed methylation sensitive qPCR assays for these regions and tested their capacity to identify the sex of turtles ranging in age between 3-34 years. The qPCR assay identified the correct sex in turtles > 17 years. However, the sex of younger turtles could not be accurately identified. This suggests the sex differences distinguishable by the assay were adult specific, reflecting the training data on which the sex-specific regions were identified, and likely linked to late-stage ontogenetic changes associated with sexual maturity. Epigenetic biomarkers are a promising tool for wildlife research because they can be minimally invasive and high throughput. Future research into sex-specific differentially methylated regions in hatchlings and juveniles should be based on genome-wide DNA methylation data from a wider age range, which includes hatchlings.

Development of SpCas9-expressing bovine mammary epithelial cell lines - Alexander J. Trevarton; Emily R. Mears; Janelle Moody; Thomas J. Lopdell; Thaize Q. Chometon; John A. Taylor; Carol J. Wang; Mathew D. Littlejohn; Russell G. Snell (In Vitro Cellular & Developmental Biology - Animal, 2023)

Diverging monthly rainfall trends in south peninsular India and their association with global climate indices - Micky Mathew; K. Sreelash; Amala Anie Jacob; Merin Mariam Mathew; D. Padmalal (Stochastic Environmental Research and Risk Assessment, 2023)

Paleodepositional and Hydrocarbon Source-Rock Characteristics of the Sonari Succession (Paleocene), Barmer Basin, NW India: Implications from Petrography and Geochemistry - Vikram P. Singh; Bhagwan D. Singh; Runcie P. Mathews; Alpana Singh; Vinod A. Mendhe; Subhashree Mishra; Mollika Banerjee (Natural Resources Research, 2022)

Evaluation and selection strategy for green supply chain using interval-valued q-rung orthopair fuzzy combinative distance-based assessment - Syed Abdul Rehman Khan; Manoj Mathew; P. D. D. Dominic; Muhammad Umar (Environment, Development and Sustainability, 2022)

First report of leaf blight of Indian spinach caused by Colletotrichum siamense in India - Sajeena Abdulmajeed; Mathew Deepu; M. K. Dhanya; John Jacob; P. Rawal; D. Jain; M. Elina; D. S. Nair; T. S. Peteti (Journal of Plant Pathology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

A Guide to International Climate Mitigation Policy and Finance Frameworks Relevant to the Protection and Restoration of Blue Carbon Ecosystems - Mathew A. Vanderklift; Dorothée Herr; Catherine E. Lovelock; Daniel Murdiyarso; Jacqueline L. Raw; Andrew D. L. Steven (Frontiers in Marine Science, 2022)
The protection, management and restoration of vegetated ecosystems on land and in the ocean (‘natural climate solutions’) can be a useful strategy for reducing net greenhouse gas emissions to help limit global warming. Their potential contribution to reducing net emissions has led to the development of policies and financial incentives for their protection and restoration. These have in turn created a set of expectations among some stakeholders, and interest in expanding these to encompass other ecosystems. However, there are specific rules about how abatement is calculated in international policy and climate finance, and the frameworks and terminology associated with them are often complex. This can be a barrier to stakeholders who want to leverage the potential of natural climate solutions, sometimes leading to incongruence between realised and anticipated benefits. In this article, we attempt to outline some of the key international policy and carbon market frameworks for coastal ‘blue carbon’ ecosystems, and the extent to which different ecosystems are accommodated. Currently, among the coastal ecosystems, only mangrove forests, seagrass meadows, and tidal marshes are typically considered in international policy and carbon market frameworks. The defining feature of these ecosystems is that the foundation species are plants that grow in sediment (soil). They are the only coastal ecosystems currently included in IPCC guidelines for national greenhouse gas inventories, and in compliance and voluntary carbon markets. There is interest in potentially including other marine ecosystems, such as kelp forests and unvegetated tidal flats, into carbon accounting frameworks, but there are unresolved questions about whether sequestration and storage of carbon by these ecosystems meets the rigorous standards required. Voluntary carbon markets have greater flexibility than mechanisms linked to national greenhouse gas inventories, and so might be early implementers of expanding methods to include other ecosystems. Incorporating coastal ecosystems into national greenhouse gas inventory is a useful action countries can take that will likely help generate incentives for protection and restoration of these important ecosystems.

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

Coconut Sugar- a Potential Storehouse of Nutritive Metabolites, Novel Bio-products and Prospects - K. B. Hebbar; S. V. Ramesh; D. K. Ghosh; P. P. Shameena Beegum; R. Pandiselvam; M. R. Manikantan; A. C. Mathew (Sugar Tech, 2022)

Stable isotope composition of multiple tissues and individual amino acids reveals dietary variation among life stages in green turtles (Chelonia mydas) at Ningaloo Reef - Jessica L. Stubbs; Andrew T. Revill; Richard D. Pillans; Mathew A. Vanderklift (Marine Biology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Internal seiches as drivers of fish depth use in lakes - Jill L. Brooks; Jonathan D. Midwood; Adam Smith; Steven J. Cooke; Bryan Flood; Christine M. Boston; Patricia Semecsen; Susan E. Doka; Mathew G. Wells (Limnology and Oceanography, 2022)
Inland temperate lakes undergo various physical processes, such as thermal stratification, that dictate the spatial availability of suitable temperature and dissolved oxygen conditions. Here, we use intensive limnological monitoring and acoustic telemetry transmitters implanted in wild fish to document the magnitude and frequency of thermocline deflection events (i.e., wind driven internal seiches that lead to upwelling of hypoxic hypolimnetic water) and their influence on freshwater fish depth use in a coastal embayment of Lake Ontario. The embayment experienced around 100 internal seiche events during a 3‐month period and tracking of walleye ( Stizostedion vitreus ) vertical positions in the water column showed clear trends of avoidance of low dissolved oxygen. Quantile regression showed a significant correlation between walleye vertical position and the depth of the 3, 4, and 5 mg L −1 oxyclines, with the 3 mg L −1 oxycline having the largest effect. Upwellings of the hypoxic hypolimnion forced walleye to use the water column above these fluctuating oxyclines (5 th percentile, p −1 oxycline. Understanding how fish respond to upwelling events (both temperature and oxygen) is important for fisheries assessment, management, and habitat restoration planning as there is clear avoidance of suboptimal oxygen conditions and sampling in the overcrowded fringes of these low‐oxygen zones could artificially inflate population estimates.

Immunoinformatics prediction of potential immunodominant epitopes from human coronaviruses and association with autoimmunity - Shilu Mathew; Aisha D. Fakhroo; Maria Smatti; Asmaa A. Al Thani; Hadi M. Yassine (Immunogenetics, 2022)

Potential of Microrhizomes for In Vitro Gingerol and Shogaol Synthesis in Ginger (Zingiber officinale Rosc.) - Manjusha Rani; M. R. Shylaja; Deepu Mathew; D. Girija; M. Asha Shankar; P. Sureshkumar; C. Beena (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

A portable recombinase polymerase amplification assay for the rapid detection of cucurbit leaf crumple virus in watermelon leaves and fruits - Melanie Kalischuk; Katherine Hendricks; Robert Hochmuth; Josh Freeman; Pamela D. Roberts; Mathews Paret (Journal of Plant Pathology, 2022)

High compliance and effective treatment of fish endoparasitic infections with oral drug delivery nanobioparticles: Safety of intestinal tissue and blood parameters - Rafael R.M. Madrid; Omar Mertins; Marcos Tavares‐Dias; Anai P. Flores‐Gonzales; Ana C.M.F. Patta; Carlos A.B. Ramirez; Vera L.S. Rigoni; Patrick D. Mathews (Journal of Fish Diseases, 2021)
Parasite infections in fish require constant surveillance and strategies for efficient treatments which guarantee the fish health, their sale value and the non‐propagation of pathogens in new environments. Fish treatments based on nanotechnology become of increasing interest since nanoparticles have been shown as efficient materials for optimizing administration of bioactives. In this study a chitosan derivative, alginate and praziquantel conjugated nanobioparticle of effective action for oral treatment of digenetic trematodes in highly infected Corydoras schwartzi was evaluated in terms of histological and hematological safety. The inherent absence of alterations in intestinal tissue and the reversible blood cells counting during a period up to 35 days showed the safety of the drug delivery nanobioparticles, which thus represent a promising strategy for effective applications in pathogens treatments by oral administration.

Evaluation of the Effectiveness of Newer Helmet Designs with Emergent Shell and Padding Technologies Versus Older Helmet Models for Preserving White Matter Following a Season of High School Football - Jed A. Diekfuss; Weihong Yuan; Jonathan A. Dudley; Christopher A. DiCesare; Matthew B. Panzer; Thomas M. Talavage; Eric Nauman; Scott Bonnette; Alexis B. Slutsky-Ganesh; Joseph Clark; Manish Anand; Mekibib Altaye; et al. (Annals of Biomedical Engineering, 2021)

Taphonomy of an excavated striped hyena (Hyaena hyaena) den in Arabia: implications for paleoecology and prehistory - Mathew Stewart; Eric Andrieux; Richard Clark-Wilson; Nils Vanwezer; James Blinkhorn; Simon J. Armitage; Abdulaziz al Omari; Badr Zahrani; Mesfer Alqahtani; Mahmoud Al-Shanti; Iyad Zalmout; Yahya S. A. Al-Mufarreh; et al. (Archaeological and Anthropological Sciences, 2021)
Studies of modern carnivore accumulations of bone (i.e., neo-taphonomy) are crucial for interpreting fossil accumulations in the archaeological and paleontological records. Yet, studies in arid regions have been limited in both number and detailed taphonomic data, prohibiting our understanding of carnivore bone-accumulating and -modifying behavior in dry regions. Here, we present a taphonomic analysis of an impressive carnivore-accumulated bone assemblage from the Umm Jirsan lava tube in the Harrat Khaybar region, Saudi Arabia. The size and composition of the bone accumulation, as well as the presence of hyena skeletal remains and coprolites, suggest that the assemblage was primarily accumulated by striped hyena ( Hyaena hyaena ). Our findings (1) identify potentially useful criteria for distinguishing between accumulations generated by different species of hyenas; (2) emphasize the need for neo-taphonomic studies for capturing the full variation in carnivore bone-accumulating and modifying behavior; (3) suggest that under the right settings, striped hyena accumulations can serve as good proxies for (paleo)ecology and livestock practices; and (4) highlight the potential for future research at Umm Jirsan, as well as at the numerous nearby lava tube systems. We encourage continued neo-taphonomic efforts in regions important in human prehistory, particularly in arid zones, which have received little research attention.

Intestinal histological alterations in farmed red-bellied pacu Piaractus brachypomus (Characiformes: Serrasalmidae) heavily infected by roundworms - Ruben C. Cuadros; Norma L. S. Rivadeneyra; Anai Flores-Gonzales; Omar Mertins; Jose C.O. Malta; M. Enrique Serrano-Martínez; Patrick D. Mathews (Aquaculture International, 2021)

Hypoxia and standing balance - Mathew I. B. Debenham; Janelle N. Smuin; Tess D. A. Grantham; Philip N. Ainslie; Brian H. Dalton (European Journal of Applied Physiology, 2021)

Long-Term Acoustic Monitoring Reveals Site Fidelity, Reproductive Migrations, and Sex Specific Differences in Habitat Use and Migratory Timing in a Large Coastal Shark (Negaprion acutidens) - Richard D. Pillans; Wayne Rochester; Russell C. Babcock; Damian P. Thomson; Michael D. E. Haywood; Mathew A. Vanderklift (Frontiers in Marine Science, 2021)
Knowledge of the movement patterns of the lemon shark Negaprion acutidens is poor in contrast to the allopatric N. brevirostis . Using acoustic telemetry, we investigated daily (diel and tidal) and seasonal patterns in residency, fidelity, home range, habitat preference, and migratory patterns along the Ningaloo coast, Australia. Thirty eight adult N. acutidens were monitored for up 6.1 years (mean 2.5 y) with 19 animals detected for more than 3 years and 5 for more than 5 y. Approximately 50% of the tagged animals remained within 10 km of their tagging location for more than 12 months (average core home range of 1.7 km 2 ). Surprisingly, residency of adults was greater than juveniles in this known nursery area. Adults showed a strong preference for lagoon habitats and moved into shallow nearshore habitats at high tide and at night. During winter months, female sharks shifted their core home range 0.45 km further offshore into deeper lagoon areas, a shift which is likely due to behavioral thermoregulation. Space use by males and females within core areas was asynchronous indicating sexual segregation by resident sharks. Both resident and non-resident sharks were detected up to 140 km away. These highly directional (southerly) and rapid movements (140 km in 2 days) were largely correlated with the parturition and mating periods with males departing 1–2 months earlier than females. In females, periodicity of migrations was variable with evidence of annual and biannual patterns. Negaprion acutidens are highly susceptible to over-fishing and movement data are essential to quantify spatio-temporal overlap with fisheries and assist with developing spatially explicit stock assessment models.

A system for rapid gene introgression into cassava immature leaves and subsequent recovery of transformed lines - Easter D. Syombua; Mark O. Adero; Wilton M. Mbinda; Christine N. Wanyonyi; Mathew P. Ngugi; Richard O. Oduor (Plant Biotechnology Reports, 2021)

Revealing the genetic diversity of maize (Zea mays L.) populations by phenotypic traits and DArTseq markers for variable resistance to fall armyworm - Chapwa Kasoma; Hussein Shimelis; Mark D. Laing; Admire I.T. Shayanowako; Isack Mathew (Genetic Resources and Crop Evolution, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Seminal fluid protein divergence among populations exhibiting postmating prezygotic reproductive isolation - Martin D. Garlovsky; Caroline Evans; Mathew A. Rosenow; Timothy L. Karr; Rhonda R. Snook (Molecular Ecology, 2020)
Despite holding a central role in fertilization, reproductive traits often show elevated rates of evolution and diversification. The rapid evolution of seminal fluid proteins (Sfps) within populations is predicted to cause mis‐signalling between the male ejaculate and the female during and after mating resulting in postmating prezygotic (PMPZ) isolation between populations. Crosses between Drosophila montana populations show PMPZ isolation in the form of reduced fertilization success in both noncompetitive and competitive contexts. Here we test whether male ejaculate proteins produced in the accessory glands or ejaculatory bulb differ between populations using liquid chromatography tandem mass spectrometry. We find more than 150 differentially abundant proteins between populations that may contribute to PMPZ isolation, including a number of proteases, peptidases and several orthologues of Drosophila melanogaster Sfps known to mediate fertilization success. Males from the population that elicit the stronger PMPZ isolation after mating with foreign females typically produced greater quantities of Sfps. The accessory glands and ejaculatory bulb show enrichment for different gene ontology (GO) terms and the ejaculatory bulb contributes more differentially abundant proteins. Proteins with a predicted secretory signal evolve faster than nonsecretory proteins. Finally, we take advantage of quantitative proteomics data for three Drosophila species to determine shared and unique GO enrichments of Sfps between taxa and which potentially mediate PMPZ isolation. Our study provides the first high‐throughput quantitative proteomic evidence showing divergence of reproductive proteins between populations that exhibit PMPZ isolation.

Spatial and temporal patterns of lateralization in a parrot species complex - Mathew L. Berg; Sarah A. Micallef; Justin R. Eastwood; Raoul F. H. Ribot; Andrew T. D. Bennett (Evolutionary Ecology, 2020)

Using Propagules to Restore Coastal Marine Ecosystems - Mathew A. Vanderklift; Christopher Doropoulos; Daniel Gorman; Inês Leal; Antoine J. P. Minne; John Statton; Andrew D. L. Steven; Thomas Wernberg (Frontiers in Marine Science, 2020)

Techno-Economic Modelling of Tidal Energy Converter Arrays in the Tacoma Narrows - Mathew B. R. Topper; Sterling S. Olson; Jesse D. Roberts (Journal of Marine Science and Engineering, 2020)
Hydrokinetic tidal energy converter (TEC) technology is yet to become cost competitive with other renewable energy sources. Understanding the interaction between energy production and the costs incurred harvesting that energy may unlock the economic potential of this technology. Although hydrodynamic simulation of TEC arrays has matured over time, including demonstration of how small and large arrays affect the resource, integration of cost modelling is often limited. The advanced ocean energy array techno-economic modelling tool ‘DTOcean’ enables designers to calculate and improve the levelised cost of energy (LCOE) of an array through parametric simulation of the energy extraction, design of the electrical network, moorings and foundations, and simulation of the installation and lifetime operations and maintenance of the array. This work presents a verification of DTOcean’s ability to simulate the techno-economic performance of TEC arrays by reproducing the hypothetical RM1 reference model, a semi-analytical model of a TEC array based in the Tacoma Narrows of Washington state, U.S.A. It is demonstrated that DTOcean can produce a reasonable estimate to the LCOE predicted by the reference model, giving (in Euro cents per kiloWatt hour) 36.69 ¢/kWh against the reference model’s 34.612 ¢/kWh for 10 TECs, while for 50 TECs, DTOcean calculated 20.34 ¢/kWh compared to 17.34 ¢/kWh for the reference model.

Dietary plasticity and the importance of salmon to brown bear (Ursus arctos) body size and condition in a low Arctic ecosystem - Lindsey S. Mangipane; Diana J. R. Lafferty; Kyle Joly; Mathew S. Sorum; Matthew D. Cameron; Jerrold L. Belant; Grant V. Hilderbrand; David D. Gustine (Polar Biology, 2020)
Ecological flexibility within animal populations can allow for variation in resource use and foraging decisions. We estimated brown bear ( Ursus arctos ) diet composition in Gates of the Arctic National Park and Preserve, Alaska from 2013 to 2015 to evaluate how variation in foraging behavior influences body condition and size. We used stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope analyses of sectioned brown bear hair samples to evaluate assimilated diet. We then developed a set of a priori linear models to evaluate differences in the diet composition of brown bears ( n = 80) in relation to body fat (%) and mass. The proportion of meat (salmon [ Oncorhynchus keta ] and terrestrial meat combined) in the diet from July through late September varied between male and female bears, with males ( $$\stackrel{-}{x}$$ x - = 62%, SD = 30) assimilating significantly more meat than females ( $$\stackrel{-}{x}$$ x - = 40%, SD = 29). Most of the meat consumed came from marine-derived resources for males (53% of the total diet or 86% of the meat) and females (31% of the total diet or 77% of the meat). As we found the range of observed diets was unrelated to physiological outcomes (i.e., percentage body fat), we suggest that ecological flexibility within populations may provide an adaptive advantage by allowing individuals to reduce competition with conspecifics by foraging on alternate food resources. Identifying variable foraging behaviors within a population can allow for a better understanding of complex behaviors and, ultimately, lead to more informed management decisions related to habitat use, development, and harvest.

Histopathology associated with infection by Procamallanus (Spirocamallanus) inopinatus (Nematoda) in farmed Brycon cephalus (Characiformes) from Peru: a potential fish health problem - Norma L. S. Rivadeneyra; Omar Mertins; Ruben C. Cuadros; Jose C. O. Malta; Lorena V. de Matos; Patrick D. Mathews (Aquaculture International, 2020)

Conceptualising and measuring psychological preparedness for disaster: The Psychological Preparedness for Disaster Threat Scale - Jim McLennan; Mathew D. Marques; Danielle Every (Natural Hazards, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Environmental friendly synthesis of zinc oxide nanoparticles and estimation of its larvicidal activity against Aedes aegypti - S. M. Roopan; R. S. Mathew; S. S. Mahesh; D. Titus; K. Aggarwal; N. Bhatia; K. I. Damodharan; K. Elumalai; J. J. Samuel (International Journal of Environmental Science and Technology, 2019)

Corrigendum: Severe Continental-Scale Impacts of Climate Change Are Happening Now: Extreme Climate Events Impact Marine Habitat Forming Communities Along 45% of Australia's Coast - Russell C. Babcock; Rodrigo H. Bustamante; Elizabeth A. Fulton; Derek J. Fulton; Michael D. E. Haywood; Alistair James Hobday; Robert Kenyon; Richard James Matear; Eva E. Plagányi; Anthony J. Richardson; Mathew A. Vanderklift (Frontiers in Marine Science, 2019)

Severe Continental-Scale Impacts of Climate Change Are Happening Now: Extreme Climate Events Impact Marine Habitat Forming Communities Along 45% of Australia’s Coast - Russell C. Babcock; Rodrigo H. Bustamante; Elizabeth A. Fulton; Derek J. Fulton; Michael D. E. Haywood; Alistair James Hobday; Robert Kenyon; Richard James Matear; Eva E. Plagányi; Anthony J. Richardson; Mathew A. Vanderklift (Frontiers in Marine Science, 2019)

Seagrass restoration in Gulf of Mannar, Tamil Nadu, Southeast India: a viable management tool - J. K. Patterson Edward; K. Diraviya Raj; G. Mathews; P. Dinesh Kumar; A. Arasamuthu; Nisha D’ Souza; Deepak S. Bilgi (Environmental Monitoring and Assessment, 2019)

3D Printing of Metformin HCl PVA Tablets by Fused Deposition Modeling: Drug Loading, Tablet Design, and Dissolution Studies - Mariam Ibrahim; Morgan Barnes; Robert McMillin; Daniel W. Cook; Sarah Smith; Mathew Halquist; Dayanjan Wijesinghe; Thomas D. Roper (AAPS PharmSciTech, 2019)

Brown bear (Ursus arctos) body size, condition, and productivity in the Arctic, 1977–2016 - Grant V. Hilderbrand; Kyle Joly; Mathew S. Sorum; Matthew D. Cameron; David D. Gustine (Polar Biology, 2019)

Prevalence of BFDV in wild breeding Platycercus elegans - Justin R. Eastwood; Mathew L. Berg; Raoul F. H. Ribot; Katherine L. Buchanan; Ken Walder; Andrew T. D. Bennett (Journal of Ornithology, 2019)

Stable Isotope Analysis Enhances Our Understanding of Diamondback Terrapin (Malaclemys terrapin) Foraging Ecology - Mathew J. Denton; Amanda W. J. Demopoulos; John D. Baldwin; Brian J. Smith; Kristen M. Hart (Estuaries and Coasts, 2019)

Plumage coloration follows Gloger's rule in a ring species - Raoul F. H. Ribot; Mathew L. Berg; Emanuel Schubert; John A. Endler; Andrew T. D. Bennett (Journal of Biogeography, 2019)
Aim Animal coloration is expected to differ between populations in different habitats according to Gloger's rule, with darker animals found in more humid, vegetated or warmer environments. Yet despite considerable support across the globe, the mechanisms behind this biogeographical rule are currently still unclear. Exploiting a ring species with plumage coloration from crimson to pale yellow, we test Gloger's rule and the mechanisms behind phenotypic divergence. Location South‐eastern Australia. Major taxa studied Crimson rosellas ( Platycercus elegans ). Methods We combined three modelling approaches (spatial regression; random decision forest species distribution and conditional inference tree) to test the association between 10 environmental variables (based on long‐term climate data and remotely sensed reflectance of the land) and plumage coloration across the distribution of P. elegans . We also took in‐situ measurements of background coloration of dominant vegetation to examine the relationship between (a) background coloration measured locally and remotely, (b) P. elegans coloration and (c) known differences in visual sensitivity of the subspecies using species‐specific visual models. Results On both a continental and a local scale, the distribution of yellow‐red plumage coloration was strongly predicted by average rainfall, summer temperature and the Earth's reflectance between 620–670 nm. Remotely sensed radiance measures correlated strongly and positively with reflectance of the leaves of the dominant tree species at sites across the P. elegans distribution. Visual modelling indicated that differences in background colour could affect signalling efficacy in dim‐light conditions. Main conclusions Our study shows that the highly variable plumage coloration conforms to Gloger's rule, and indicates that background coloration of the vegetation and thermoregulation are likely to be important mechanisms. Our results also show that Gloger's rule can explain variation in pigmentary systems other than melanin, and highlight that selection from environmental variation could be an important force behind the geographic diversity found in ring species.

Nutrient availability in the Setiu Wetland Lagoon, Malaysia: trends, possible causes and environmental impacts - S. C. Poh; N. C. W. Ng; S. Suratman; D. Mathew; N. Mohd Tahir (Environmental Monitoring and Assessment, 2019)

On the Applicability of Nadai and Mogi Failure Criteria to Porous Sandstones - Xiaodong Ma; Mathew D. Ingraham (Rock Mechanics and Rock Engineering, 2018)

Future Directions in the Research and Management of Marine Snakes - Vinay Udyawer; Peter Barnes; Xavier Bonnet; François Brischoux; Jenna M. Crowe-Riddell; Blanche D’Anastasi; Bryan G. Fry; Amber Gillett; Claire Goiran; Michael L. Guinea; Harold Heatwole; Michelle R. Heupel; et al. (Frontiers in Marine Science, 2018)

Morphology and surface ultrastructure of Dadaytrema oxycephala (Digenea: Cladorchiidae) with a new host record from Peruvian Amazon floodplain - Ruben C. Cuadros; Norma L. S. Rivadeneyra; José C. O. Malta; M. Enrique Serrano-Martínez; Patrick D. Mathews (Biologia, 2018)

Plasticity in physiological condition of female brown bears across diverse ecosystems - Grant V. Hilderbrand; David D. Gustine; Buck Mangipane; Kyle Joly; William Leacock; Lindsey Mangipane; Joy Erlenbach; Mathew S. Sorum; Matthew D. Cameron; Jerrold L. Belant; Troy Cambier (Polar Biology, 2018)

Rock art provides new evidence on the biogeography of kudu ( Tragelaphus imberbis ), wild dromedary, aurochs ( Bos primigenius ) and African wild ass ( Equus africanus ) in the early and middle Holocene of north‐western Arabia - Maria Guagnin; Ceri Shipton; Sarah el‐Dossary; Moudhy al‐Rashid; Farès Moussa; Mathew Stewart; Florian Ott; Abdullah Alsharekh; Michael D. Petraglia (Journal of Biogeography, 2018)
Aim Our knowledge of the prehistoric distribution of animal species is so far largely dependent on the location of excavated archaeological and palaeontological sites. In the absence of excavated faunal remains, many species that were present in the Levant and North Africa have been assumed to have been absent on the Arabian Peninsula. Here, we explore representations of four species that were identifiable in the rock art, but had not previously been reported in north‐western Arabia. Location Jubbah and Shuwaymis UNESCO world heritage rock art sites in Ha'il province, north‐western Saudi Arabia. Methods In total, the rock art panels surveyed and recorded in Jubbah and Shuwaymis contain 6,618 individual animal depictions. Species were identified based on diagnostic features of the anatomy. The resulting dataset was then compared to the faunal spectrum reported in the (archaeo)zoological literature. Results The rock art dataset provides evidence that the distributions of lesser kudu ( Tragelaphus imberbis ), wild camel and African wild ass ( Equus africanus ) extended into the north‐west of Arabia and that the engravers may have had knowledge of aurochs ( Bos primigenius ). Main conclusions The presence of previously undocumented mammal species in Arabia provides new information regarding their distribution, as well as the types of habitat and vegetation that were available in prehistoric landscapes. Moreover, the presence of kudu on the Arabian Peninsula indicates that the identification of palaeo‐distributions based exclusively on faunal remains may miss key species in the Afro‐Eurasian faunal exchange.

The Effect of Non-Stroke Cardiovascular Disease States on Risk for Cognitive Decline and Dementia: A Systematic and Meta-Analytic Review - Kayla B. Stefanidis; Christopher D. Askew; Kim Greaves; Mathew J. Summers (Neuropsychology Review, 2018)

Interrogating marine virus‐host interactions and elemental transfer with BONCAT and nanoSIMS‐based methods - Alexis L. Pasulka; Kimberlee Thamatrakoln; Sebastian H. Kopf; Yunbin Guan; Bonnie Poulos; Annie Moradian; Michael J. Sweredoski; Sonja Hess; Mathew B. Sullivan; Kay D. Bidle; Victoria J. Orphan (Environmental Microbiology, 2018)
Summary While the collective impact of marine viruses has become more apparent over the last decade, a deeper understanding of virus‐host dynamics and the role of viruses in nutrient cycling would benefit from direct observations at the single‐virus level. We describe two new complementary approaches – stable isotope probing coupled with nanoscale secondary ion mass spectrometry (nanoSIMS) and fluorescence‐based biorthogonal non‐canonical amino acid tagging (BONCAT) – for studying the activity and biogeochemical influence of marine viruses. These tools were developed and tested using several ecologically relevant model systems ( Emiliania huxleyi /EhV207, Synechococcus sp . WH8101/Syn1 and Escherichia coli /T7). By resolving carbon and nitrogen enrichment in viral particles, we demonstrate the power of nanoSIMS tracer experiments in obtaining quantitative estimates for the total number of viruses produced directly from a particular production pathway (by isotopically labelling host substrates). Additionally, we show through laboratory experiments and a pilot field study that BONCAT can be used to directly quantify viral production (via epifluorescence microscopy) with minor sample manipulation and no dependency on conversion factors. This technique can also be used to detect newly synthesized viral proteins. Together these tools will help fill critical gaps in our understanding of the biogeochemical impact of viruses in the ocean.

Emerging Technologies and Synergies for Airborne and Space-Based Measurements of Water Vapor Profiles - Amin R. Nehrir; Christoph Kiemle; Mathew D. Lebsock; Gottfried Kirchengast; Stefan A. Buehler; Ulrich Löhnert; Cong-Liang Liu; Peter C. Hargrave; Maria Barrera-Verdejo; David M. Winker (Surveys in Geophysics, 2017)
A deeper understanding of how clouds will respond to a warming climate is one of the outstanding challenges in climate science. Uncertainties in the response of clouds, and particularly shallow clouds, have been identified as the dominant source of the discrepancy in model estimates of equilibrium climate sensitivity. As the community gains a deeper understanding of the many processes involved, there is a growing appreciation of the critical role played by fluctuations in water vapor and the coupling of water vapor and atmospheric circulations. Reduction of uncertainties in cloud-climate feedbacks and convection initiation as well as improved understanding of processes governing these effects will result from profiling of water vapor in the lower troposphere with improved accuracy and vertical resolution compared to existing airborne and space-based measurements. This paper highlights new technologies and improved measurement approaches for measuring lower tropospheric water vapor and their expected added value to current observations. Those include differential absorption lidar and radar, microwave occultation between low-Earth orbiters, and hyperspectral microwave remote sensing. Each methodology is briefly explained, and measurement capabilities as well as the current technological readiness for aircraft and satellite implementation are specified. Potential synergies between the technologies are discussed, actual examples hereof are given, and future perspectives are explored. Based on technical maturity and the foreseen near-mid-term development path of the various discussed measurement approaches, we find that improved measurements of water vapor throughout the troposphere would greatly benefit from the combination of differential absorption lidar focusing on the lower troposphere with passive remote sensors constraining the upper-tropospheric humidity.

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Telemetry-Determined Habitat Use Informs Multi-Species Habitat Management in an Urban Harbour - Andrew M. Rous; Jonathon D. Midwood; Lee F.G. Gutowsky; Nicolas W.R. Lapointe; Rick Portiss; Thomas Sciscione; Mathew G. Wells; Susan E. Doka; Steven J. Cooke (Environmental Management, 2017)

Micronutrient Composition of 35 Food Fishes from India and Their Significance in Human Nutrition - Bimal P. Mohanty; T. V. Sankar; Satabdi Ganguly; Arabinda Mahanty; R. Anandan; Kajal Chakraborty; B. N. Paul; Debajit Sarma; J. Syama Dayal; Suseela Mathew; K. K. Asha; Tandrima Mitra; et al. (Biological Trace Element Research, 2016)

Hypocretin/orexin antagonism enhances sleep-related adenosine and GABA neurotransmission in rat basal forebrain - Jacqueline Vazquez-DeRose; Michael D. Schwartz; Alexander T. Nguyen; Deepti R. Warrier; Srishti Gulati; Thomas K. Mathew; Thomas C. Neylan; Thomas S. Kilduff (Brain Structure and Function, 2016)

Mouse genome annotation by the RefSeq project - Kelly M. McGarvey; Tamara Goldfarb; Eric Cox; Catherine M. Farrell; Tripti Gupta; Vinita S. Joardar; Vamsi K. Kodali; Michael R. Murphy; Nuala A. O’Leary; Shashikant Pujar; Bhanu Rajput; Sanjida H. Rangwala; et al. (Mammalian Genome, 2015)
Complete and accurate annotation of the mouse genome is critical to the advancement of research conducted on this important model organism. The National Center for Biotechnology Information (NCBI) develops and maintains many useful resources to assist the mouse research community. In particular, the reference sequence (RefSeq) database provides high-quality annotation of multiple mouse genome assemblies using a combinatorial approach that leverages computation, manual curation, and collaboration. Implementation of this conservative and rigorous approach, which focuses on representation of only full-length and non-redundant data, produces high-quality annotation products. RefSeq records explicitly link sequences to current knowledge in a timely manner, updating public records regularly and rapidly in response to nomenclature updates, addition of new relevant publications, collaborator discussion, and user feedback. Whole genome re-annotation is also conducted at least every 12–18 months, and often more frequently in response to assembly updates or availability of informative data. This article highlights key features and advantages of RefSeq genome annotation products and presents an overview of NCBI processes to generate these data. Further discussion of NCBI’s resources highlights useful features and the best methods for accessing our data.

New onset executive function difficulties at menopause: a possible role for lisdexamfetamine - C. Neill Epperson; Sheila Shanmugan; Deborah R. Kim; Sarah Mathews; Kathryn A. Czarkowski; Jeanette Bradley; Dina H. Appleby; Claudia Iannelli; Mary D. Sammel; Thomas E. Brown (Psychopharmacology, 2015)

Linking place-based science to people through spatial narratives of coastal stewardship - J. Silbernagel; G. Host; C. Hagley; D. Hart; R. Axler; R. Fortner; M. Axler; V. Smith; A. Drewes; W. Bartsch; N. Danz; J. Mathews; et al. (Journal of Coastal Conservation, 2015)

Pharmacokinetics, Antitumor and Cardioprotective Effects of Liposome-Encapsulated Phenylaminoethyl Selenide in Human Prostate Cancer Rodent Models - Jeong Yeon Kang; Mathew Eggert; Shravanthi Mouli; Ibrahim Aljuffali; Xiaoyu Fu; Ben Nie; Amy Sheil; Kendall Waddey; Charlie D. Oldham; Sheldon W. May; Rajesh Amin; Robert D. Arnold (Pharmaceutical Research, 2015)

Altered snowfall and soil disturbance influence the early life stage transitions and recruitment of a native and invasive grass in a cold desert - Elise S. Gornish; Zachary T. Aanderud; Roger L. Sheley; Mathew J. Rinella; Tony Svejcar; Suzanne D. Englund; Jeremy J. James (Oecologia, 2015)

Whole-genome analyses of DS-1-like human G2P[4] and G8P[4] rotavirus strains from Eastern, Western and Southern Africa - Martin M. Nyaga; Karla M. Stucker; Mathew D. Esona; Khuzwayo C. Jere; Bakari Mwinyi; Annie Shonhai; Enyonam Tsolenyanu; Augustine Mulindwa; Julia N. Chibumbya; Hokororo Adolfine; Rebecca A. Halpin; Sunando Roy; et al. (Virus Genes, 2014)

Integrating intensity–duration-based rainfall threshold and antecedent rainfall-based probability estimate towards generating early warning for rainfall-induced landslides in parts of the Garhwal Himalaya, India - John Mathew; D. Giri Babu; S. Kundu; K. Vinod Kumar; C. C. Pant (Landslides, 2014)

Business analysis and market potential of drug screening technology for preventive and personalized therapy - Igor V Volchek; Philip D Cotter; Andrei S Petrov; Mathew W Moore (EPMA Journal, 2014)

A novel rearrangement of occludin causes brain calcification and renal dysfunction - Marissa A. LeBlanc; Lynette S. Penney; Daniel Gaston; Yuhao Shi; Erika Aberg; Mathew Nightingale; Haiyan Jiang; Roxanne M. Gillett; Somayyeh Fahiminiya; Christine Macgillivray; Ellen P. Wood; Philip D. Acott; et al. (Human Genetics, 2013)

Reversible immobilization of free‐ranging adult male California sea lions ( Zalophus californianus ) - Sharon R. Melin; Martin Haulena; William Van Bonn; Mathew J. Tennis; Robin F. Brown; Jeffrey D. Harris (Marine Mammal Science, 2013)

Predictors of regional establishment success and spread of introduced non‐indigenous vertebrates - Craig R. Allen; Kristine T. Nemec; Donald A. Wardwell; Justin D. Hoffman; Mathew Brust; Karie L. Decker; Daniel Fogell; Jennifer Hogue; Aaron Lotz; Thaddeus Miller; Marcy Pummill; Luis E. Ramirez‐Yañez; et al. (Global Ecology and Biogeography, 2013)
Aim To provide the first analysis of predictors of both establishment and spread, both within and across taxa, for all vertebrate taxa within a region. We used F lorida, USA , as our study system because it has a well‐documented history of introduction and invasion, and is a hotspot for biological invasions. Location F lorida, USA. Methods We analysed non‐indigenous species ( NIS ) data from peninsular F lorida – which included both successful and unsuccessful introductions from all vertebrate classes – to determine the best predictors of both establishment and spread for fish (65 species), herpetofauna (63 species), birds (71 species) and mammals (25 species). We used 10 variables proposed to be associated with the establishment and spread of NIS : body mass, geographic origin, reproductive rate, diet generalism, native‐range size, latitude of native range, number of NIS present at date of introduction, presence of NIS congeners, morphological proximity to other NIS (in terms of body mass) and propagule pressure. A multimodel selection process was used with an information‐theoretic approach to determine the best fit models for predicting establishment and spread of NIS . We selected a priori plausible predictive models for establishment and spread. Results Large native‐range size and small body mass best predicted establishment of non‐indigenous herpetofauna. The presence of NIS congeners had the largest positive effect on the establishment of non‐indigenous fish. For mammals, the number of NIS present at the time of introduction best explained establishment. No single model best explained bird establishment. For all taxa but birds, the number of NIS present at time of introduction was included in at least one of the best‐supported models for explaining spread. Main conclusions Our analyses suggest that predictors of establishment and spread differ across vertebrate taxa at the scale studied. Most predictive variables can be interpreted as measures of competitive interactions among species.

From bonito to anchovy: a reconstruction of Turkey’s marine fisheries catches (1950-2010) - A. ULMAN; S. BEKISOGLU; M.A ZENGIN; S. KNUDSEN; V. UNAL; C. MATHEWS; S. HARPER; D. ZELLER; D. PAULY (Mediterranean Marine Science, 2013)
Turkey’s marine fisheries catches were estimated for the 1950-2010 time period using a reconstruction approach, which estimated all fisheries removals, including unreported landings, recreational landings and discards. We added these estimates to the ‘official’ data, as reported in TURKSTAT, which are also available from the United Nation’s Food and Agriculture Organization (FAO). The total reconstructed catch for the 1950-2010 time period (inclusive of the reported data) is approximately 32 million t, or 74% more than the 18.4 million t of reported data. This added approximately 13.6 million t to the reported data, consisting of 6.9 million t of unreported landings, 2.6 million t of discards, 2.4 million t of recreational catches, and 1.7 million t of subsistence catches. In 2010, total reported marine landings for Turkey were 445,680 t and the total reconstructed catch was 763,760 t, or 73% more than the reported data. The main unreported taxon by tonnage was European anchovy (Engraulis encrasicolus) due to its sheer high proportion of catch. The major reasons for underreporting include a general distrust fishers have towards the taxing system combined with inefficient fisheries monitoring and surveillance capabilities. Accounting for all fisheries components is crucial in understanding the development of fisheries resources, improving management, and reducing threats to the domestic food security of Turkey.

Evaluating genetic markers and neurobiochemical analytes for fluoxetine response using a panel of mouse inbred strains - Cristina S. Benton; Brooke H. Miller; Sean Skwerer; Oscar Suzuki; Laura E. Schultz; Michael D. Cameron; J. S. Marron; Mathew T. Pletcher; Tim Wiltshire (Psychopharmacology, 2012)

Analysis of quantitative disease resistance to southern leaf blight and of multiple disease resistance in maize, using near-isogenic lines - Araby R. Belcher; John C. Zwonitzer; Jose Santa Cruz; Mathew D. Krakowsky; Chia-Lin Chung; Rebecca Nelson; Consuelo Arellano; Peter J. Balint-Kurti (Theoretical and Applied Genetics, 2012)

Radiative forcing of natural forest disturbances - Thomas L. O'Halloran; Beverly E. Law; Michael L. Goulden; Zhuosen Wang; Jordan G. Barr; Crystal Schaaf; Mathew Brown; José D. Fuentes; Mathias Göckede; Andrew Black; Vic Engel (Global Change Biology, 2012)
Forest disturbances are major sources of carbon dioxide to the atmosphere, and therefore impact global climate. Biogeophysical attributes, such as surface albedo (reflectivity), further control the climate‐regulating properties of forests. Using both tower‐based and remotely sensed data sets, we show that natural disturbances from wildfire, beetle outbreaks, and hurricane wind throw can significantly alter surface albedo, and the associated radiative forcing either offsets or enhances the CO 2 forcing caused by reducing ecosystem carbon sequestration over multiple years. In the examined cases, the radiative forcing from albedo change is on the same order of magnitude as the CO 2 forcing. The net radiative forcing resulting from these two factors leads to a local heating effect in a hurricane‐damaged mangrove forest in the subtropics, and a cooling effect following wildfire and mountain pine beetle attack in boreal forests with winter snow. Although natural forest disturbances currently represent less than half of gross forest cover loss, that area will probably increase in the future under climate change, making it imperative to represent these processes accurately in global climate models.

Absorbance of retinal oil droplets of the budgerigar: sex, spatial and plumage morph-related variation - Ben Knott; James K. Bowmaker; Mathew L. Berg; Andrew T. D. Bennett (Journal of Comparative Physiology A, 2012)

Uniformity of rotavirus strain nomenclature proposed by the Rotavirus Classification Working Group (RCWG) - Jelle Matthijnssens; Max Ciarlet; Sarah M. McDonald; Houssam Attoui; Krisztián Bányai; J. Rodney Brister; Javier Buesa; Mathew D. Esona; Mary K. Estes; Jon R. Gentsch; Miren Iturriza-Gómara; Reimar Johne; et al. (Archives of Virology, 2011)

Intracerebral source generators characterizing concentrative meditation - Christina F. Lavallee; Mathew D. Hunter; Michael A. Persinger (Cognitive Processing, 2011)

Estimating parameters of a forest ecosystem C model with measurements of stocks and fluxes as joint constraints - Andrew D. Richardson; Mathew Williams; David Y. Hollinger; David J. P. Moore; D. Bryan Dail; Eric A. Davidson; Neal A. Scott; Robert S. Evans; Holly Hughes; John T. Lee; Charles Rodrigues; Kathleen Savage (Oecologia, 2010)

Plant-soil biodiversity relationships and nutrient retention in agricultural riparian zones of the Sacramento Valley, California - Anna Young-Mathews; Steven W. Culman; Sara Sánchez-Moreno; A. Toby O’Geen; Howard Ferris; Allan D. Hollander; Louise E. Jackson (Agroforestry Systems, 2010)

Genetic characterization of 2006–2008 isolates of Chikungunya virus from Kerala, South India, by whole genome sequence analysis - E. Sreekumar; Aneesh Issac; Sajith Nair; Ramkumar Hariharan; M. B. Janki; D. S. Arathy; R. Regu; Thomas Mathew; M. Anoop; K. P. Niyas; M. R. Pillai (Virus Genes, 2010)

Erratum to: Molecular characterization of a rare, human-porcine reassortant rotavirus strain, G11P[6], from Ecuador - Krisztián Bányai; Mathew D. Esona; Tara K. Kerin; Jennifer J. Hull; Slavica Mijatovic; Nancy Vásconez; Carlos Torres; Ana M. B. de Filippis; Kimberly R. Foytich; Jon R. Gentsch (Archives of Virology, 2010)

Molecular characterization of a rare, human-porcine reassortant rotavirus strain, G11P[6], from Ecuador - Krisztián Bányai; Mathew D. Esona; Tara K. Kerin; Jennifer J. Hull; Slavica Mijatovic; Nancy Vásconez; Carlos Torres; Ana M. B. de Filippis; Jon R. Gentsch (Archives of Virology, 2009)

Post-harvest deterioration of sugarcane with special reference to quality loss - P. Rakkiyappan; D. Esther Shekinah; P. Gopalasundaram; M. D. Mathew; S. Asokan (Sugar Tech, 2009)

Positron emission tomographic studies of brain dopamine and serotonin transporters in abstinent (±)3,4-methylenedioxymethamphetamine (“ecstasy”) users: relationship to cognitive performance - Una D. McCann; Zsolt Szabo; Melin Vranesic; Michael Palermo; William B. Mathews; Hayden T. Ravert; Robert F. Dannals; George A. Ricaurte (Psychopharmacology, 2008)

Simulated glacial and interglacial vegetation across Africa: implications for species phylogenies and trans‐African migration of plants and animals - SHARON A. COWLING; PETER M. COX; CHRIS D. JONES; MARK A. MASLIN; MATHEW PEROS; STEVEN A. SPALL (Global Change Biology, 2008)
The paleoenvironmental context of plant and animal species evolution (including glacial migrations and population separations) is based on a very patchy and incomplete paleo‐phytogeographic record. It was our objective, therefore, to provide an additional source for paleovegetation comparison by presenting simulations from a state‐of‐the‐art fully coupled earth system model (HadCM3LC). We simulated potential paleovegetation distributions following pre‐Industrial and last glacial maximum (LGM) climate forcing for the continent of Africa. Our LGM simulations indicate that tropical broadleaf forest was not severely displaced by expanding grasslands within central Africa, although the outer extent of closed forest decreases, particularly in the north. Our simulations indicate that the structure of glacial forests may have been much different from today, in that LGM simulations indicate that forests were likely characterized by lower leaf area indexes, lower tree heights and lower vegetation carbon content. On the other hand, warmer interglacial climate (like our pre‐Industrial climate scenario) results in simulated expansion of tropical forest from coast to coast across central Africa that we postulate could have acted as a barrier to plant and animal species migrations. We suggest that our modeling experiments have implications for the interpretation of phylogenetic data, including that of our own species, Homo sapiens sapiens .

Limestone Neutralisation of Arsenic-Rich Effluent from a Gold Mine - M. de Beer; E. H. Mathews; D. Krueger; J. Maree; N. Mbhele; M. Phalanndwa; O. Novhe (Mine Water and the Environment, 2008)

Characterization of a SEPT9 interacting protein, SEPT14, a novel testis-specific septin - Esther A. Peterson; Linda M. Kalikin; Jonathan D. Steels; Mathew P. Estey; William S. Trimble; Elizabeth M. Petty (Mammalian Genome, 2007)

Comparative analyses reveal high levels of conserved colinearity between the finger millet and rice genomes - Srinivasachary; Mathews M. Dida; Mike D. Gale; Katrien M. Devos (Theoretical and Applied Genetics, 2007)

Revisiting the Links between Governance and Biodiversity Loss - Christopher B. Barrett; Clark C. Gibson; Barak Hoffman; Mathew D. McCub‐bins (Conservation Biology, 2007)

Winter-spring precipitation reconstructions from tree rings for northeast Mexico - Jose Villanueva-Diaz; David W. Stahle; Brian H. Luckman; Julian Cerano-Paredes; Mathew D. Therrell; Malcom K. Cleaveland; Eladio Cornejo-Oviedo (Climatic Change, 2007)

Evaluation of ogawa passive sampling devices as an alternative measurement method for the nitrogen dioxide annual standard in El Paso, Texas - Mark E. Sather; E. Terrence Slonecker; Johnson Mathew; Hunter Daughtrey; Dennis D. Williams (Environmental Monitoring and Assessment, 2007)

The genetic map of finger millet, Eleusine coracana - Mathews M. Dida; Srinivasachary; Sujatha Ramakrishnan; Jeffrey L. Bennetzen; Mike D. Gale; Katrien M. Devos (Theoretical and Applied Genetics, 2006)

The Complex Links between Governance and Biodiversity - CHRISTOPHER B. BARRETT; CLARK C. GIBSON; BARAK HOFFMAN; MATHEW D. McCUBBINS (Conservation Biology, 2006)
We argue that two problems weaken the claims of those who link corruption and the exploitation of natural resources. The first is conceptual and the second is methodological. Studies that use national‐level indicators of corruption fail to note that corruption comes in many forms, at multiple levels, that may affect resource use quite differently: negatively, positively, or not at all. Without a clear causal model of the mechanism by which corruption affects resources, one should treat with caution any estimated relationship between corruption and the state of natural resources. Simple, atheoretical models linking corruption measures and natural resource use typically do not account for other important control variables pivotal to the relationship between humans and natural resources. By way of illustration of these two general concerns, we used statistical methods to demonstrate that the findings of a recent, well‐known study that posits a link between corruption and decreases in forests and elephants are not robust to simple conceptual and methodological refinements. In particular, once we controlled for a few plausible anthropogenic and biophysical conditioning factors, estimated the effects in changes rather than levels so as not to confound cross‐sectional and longitudinal variation, and incorporated additional observations from the same data sources, corruption levels no longer had any explanatory power.

Hydrography and water masses in the southeastern Arabian Sea during March–June 2003 - S. S. C. Shenoi; D. Shankar; G. S. Michael; J. Kurian; K. K. Varma; M. R. Ramesh Kumar; A. M. Almeida; A. S. Unnikrishnan; W. Fernandes; N. Barreto; C. Gnanaseelan; R. Mathew; et al. (Journal of Earth System Science, 2005)

Application of a quartz crystal microbalance to evaluate biodegradability of starch by Bacillus subtilis - M. Jenkins; M. Horsfall; D. Mathew; M. Scanlon; R. Jayasekara; G.T. Lonergan (Biotechnology Letters, 2004)

Genetic, ecological, and behavioural divergence between two sibling snapping shrimp species (Crustacea: Decapoda: Alpheus ) - L. M. Mathews; C. D. Schubart; J. E. Neigel; D. L. Felder (Molecular Ecology, 2002)
Examination of genetic and ecological relationships within sibling species complexes can provide insights into species diversity and speciation processes. Alpheus angulatus and A. armillatus , two snapping shrimp species with overlapping ranges in the north‐western Atlantic, are similar in morphology, exploit similar ecological niches and appear to represent recently diverged sibling species. We examined phylogenetic and ecological relationships between these two species with: (i) sequence data from two mitochondrial genes (16 S rRNA and COI ); (ii) data on potential differences in microhabitat distribution for A. armillatus and A. angulatus ; and (iii) data from laboratory experiments on the level of reproductive isolation between the two species. DNA sequence data suggest A. armillatus and A. angulatus are sister species that diverged subsequent to the close of the Isthmus of Panama, and that haplotype diversity is lower in A. armillatus than in A. angulatus . Both species are distantly related to A. heterochaelis and A. estuariensis , two species with which A. angulatus shares some similarities in coloration. Ecological data on the distribution of A. angulatus and A. armillatus from two locations revealed differences in distribution of the two species between habitat patches, with each patch dominated by one or the other species. However, there was no apparent difference in distribution of the two species within habitat patches with respect to microhabitat location. Ecological data also revealed that heterospecific individuals often occur in close proximity (i.e. within metres or centimetres) where sympatric. Behavioural data indicated that these species are reproductively isolated, which is consistent with speciation in transient allopatry followed by post‐divergence secondary contact. Our data further resolve taxonomic confusion between the sibling species, A. armillatus and A. angulatus , and suggest that sympatry in areas of range overlap and exploitation of similar ecological niches by these two recently diverged species have selected for high levels of behavioural incompatibility.

Analysis of single-nucleotide polymorphisms in the interleukin-4 receptor gene for association with inflammatory bowel disease - M. Olavesen; J. Hampe; M. M. Mirza; R. Saiz; C. M. Lewis; S. Bridger; D. Teare; D. F. Easton; T. Herrmann; G. Scott; J. Hirst; J. Sanderson; et al. (Immunogenetics, 2000)

Components of yield and quality in intraspecific hybrids ofSaccharum officinarum L. selected for ancillary uses - N. V. Nair; R. Nagarajan; M. D. Mathew; T. V. Sreenivasan (Sugar Tech, 1999)

MHC characterization of ALR and ALS mice: respective similarities to the NOD and NON strains - Robert T. Graser; Clayton E. Mathews; Edward H. Leiter; D. V. Serreze (Immunogenetics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

An Ecology‐Based Method for Defining Priorities for Large Mammal Conservation: The Tiger as Case Study - Eric D. Wikramanayake; Eric Dinerstein; John G. Robinson; Ullas Karanth; Alan Rabinowitz; David Olson; Thomas Mathew; Prashant Hedao; Melissa Conner; Ginette Hemley; Dorene Bolze (Conservation Biology, 1998)
The disappearance of large vertebrates in the tropical belt may be the next biological insult of the global extinction crisis. Large predators and their prey are at particular risk in Asia, where they are threatened by poaching and habitat loss. To facilitate the best use of limited conservation resources, we created an objective, ecology‐based method for identifying priority areas for conservation that incorporates both habitat representation and landscape‐level features. Using tigers as an example, our method captures the range of ecological habitats where they occur, accounting for ecological, demographic, genetic, and behavioral differences. Our analysis is hierarchical. We divided the tiger range into distinct bioregions and identified tiger habitat types within each. We then delineated tiger conservation units throughout the bioregions and ranked the units based on habitat integrity, poaching pressure, and tiger population trends. To maintain representation of tiger populations and their ecology in the different tiger habitats, we made comparisons only among tiger conservation units from the same tiger habitat types nested within the same bioregion. We identified 159 tiger conservation units in three bioregions—the Indian subcontinent, Indochina, and Southeast Asia. We ranked the units in three categories that reflect the probability of long‐term persistence of tiger populations ( highest in level I units). Twenty‐five tiger conservation units were classified as level I, 21 as level II, and 97 as level III. An additional 16 tiger conservation units for which little information is available were identified for immediate surveys. Levels I , II, and those identified for immediate surveys are the priority areas for immediate funding and for a regional tiger conservation strategy. One feature emerging from the study showed that protected areas cover only small areas of tiger conservation units. If the long‐term prospects for tiger conservation are to improve, poaching must be stopped and protected areas increased in number, linked, and buffered by natural habitats. To enhance landscape integrity, the priority tiger conservation units that straddle international borders should be managed as transboundary reserves, giving tiger conservation a stronger regional structure. Like tigers, populations of other wide‐ranging mammalian carnivores and large herbivores also are declining due to poaching and loss of habitat. The method we present for tigers can be adapted readily to improve conservation strategies for these species as well. Método con Bases Ecológicas para Definir Prioridades para la Conservación de Mamíferos Mayores: El Tigre como Caso de Estudio La desaparición de vertebrados grandes en el cinturón tropical podría ser el siguiente insulto biológico de la crisis de exteinción global. Los depredadores grandes y sus presas se encuentran en un riesgo particular en Asia donde la caza furtiva y la pérdida de hábitats los amenaza. Para facilitar el mejor uso de los limitados recursos de conservación, hemos creado un método objetivo con bases ecológicas que incorpora tanto la representación del hábitat, como las características a nivel de paisaje en la identificación de áreas prioritarias para conservación. Utilizando tigres como ejemplo, nuestro método captura el rango de hábitats ecológicos donde los tigres pueden estar presentes tomando en cuenta diferencias ecológicas, demográficas, genéticas y de conducta. Nuestro análisis es jerárquico. Dividimos el rango de los tigres en bioregiones distintas e identificamos tipos de hábitat para tigres dentro de estas regiones. Posteriormente delineamos unidades de conservación de tigres a lo largo de las bioregiones y organizamos por rangos las unidades en base a la integridad del hábitat, presión por caza furtiva y tendencias de las poblaciones de tigres. Para mantener la representación de las poblaciones de tigres y su ecología en los diferentes hábitats, únicamente hicimos comparaciones entre unidades de conservación de tigres del mismo tipo de hábitat para tigres, anidados dentro de una misma bioregión. Identificamos 159 unidades de conservación de tigres en tres bioregiones—el subcontinente Indú, Indochina y Sur de Asia. Organizamos por rangos las unidades en tres categorías que reflejan la probabilidad de persistencia a largo plazo de poblaciones de tigres (los mayores en unidades de nivel I). Veinticinco unidades de conservación de tigres fueron clasificadas como nivel I, 21 como nivel II y 97 como nivel III. Dieciséis unidades de conservación de tigres adicionales con poca información viable fueron identificadas para muestreo inmediato. Los niveles I y II y aquellos identificados como muestreos inmediatos son áreas prioritarias para financiamiento immediato y para una estrategia de conservación de tigres. Una característica emergente en el estudio muestra que áreas protegidas cubren únicamente áreas pequeñas de unidades de conservación de tigres. Si las perspectivas a largo plazo para la conservación de tigres van a mejorar, la caza ilegal debe ser detenida y las áreas protegidas incrementadas en número, ligadas y amortiguadas por hábitats naturales. Para mejorar la integridad del paisaje, las unidades prioritarias de conservación de tigres que presentan fronteras internacionales deberán ser manejadas como reservas transfronterizas otorgándole a la conservación de tigres una etsructura regional mas fuerte. Así como los tigres, poblaciones de otros carnívoros de amplio rango y herbívoros grandes estan en disminución debido a la caza furtiva y la pérdida del hábitat. El método que presentamos para tigres puede ser adaptado fácilmente para mejorar también las estrategias de conservación de estas especies.

An Ecology-Based Method for Defining Priorities for Large Mammal Conservation: The Tiger as Case Study - Eric D. Wikramanayake; Eric Dinerstein; John G. Robinson; Ullas Karanth; Alan Rabinowitz; David Olson; Thomas Mathew; Prashant Hedao; Melissa Conner; Ginette Hemley; Dorene Bolze (Conservation Biology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

The mouse homolog of FRG1, a candidate gene for FSHD, maps proximal to the myodystrophy mutation on chromosome 8 - Prabhjit K. Grewal; Judith C. T. van Deutekom; Kate A. Mills; Richard J. L. F. Lemmers; Kathy D. Mathews; Rune R. Frants; Jane E. Hewitt (Mammalian Genome, 1997)

Wood preservative leachates from docks in an estuarine environment - P. H. Wendt; R. F. Van Dolah; M. Y. Bobo; T. D. Mathews; M. V. Levisen (Archives of Environmental Contamination and Toxicology, 1996)

Wood Preservative Leachates from Docks in an Estuarine Environment - P. H. Wendt; R. F. Van Dolah; M. Y. Bobo; T. D. Mathews; M. V. Levisen (Archives of Environmental Contamination and Toxicology, 1996)